And now everything is supposed to be normal again – just like that?! : Mixed emotions and negotiations of careers and performer identities after the pandemic (Sociologisk Forskning, 2024)
The global pandemic of Covid-19 has had massive effects on many levels. For many sectors, the restrictions are gone but normalcy is not fully restored. The performing arts, for example, have been especially vulnerable to sharp restrictions, with audiences staying at home. The aim of this article is to explore what it means for freelance musicians in the art/classical music genre to re-establish their careers after the pandemic. The empirical data consists of interviews with Swedish freelance musicians from 2021 and 2022. The article concludes that the pandemic and its aftermath present the freelancers with substantial practical challenges and emotional dilemmas. Some of the freelancers have been able to re-establish their careers and performer identities, while others are still struggling to get back into the loop. The pandemic has started processes of change, which are now negotiated in relation to going back to ‘normal’.
Keywords: freelance musicians; post-pandemic transitions; negotiations; mixed emotions; careers and performer identities